Seasonal variations in carbon, nitrogen, and phosphorus of Pinus yunnanenis at different stand ages - Liang, Siyi; Tan, Tian; Wu, Danzi; Li, Chaojun; Jing, Huiqing; Wu, Junwen (Frontiers in Plant Science, 2023)
The seasonal variations in carbon (C), nitrogen (N), and phosphorus (P) at the organ level of Pinus yunnanenis during different growth stages are poorly understood. In this study, the C, N, P, and their stoichiometric ratios in various organs of P. yunnanensis during the four seasons are discussed. The middle and young aged P. yunnanensis forests in central Yunnan province, China were chosen, and the contents of C, N, and P in fine roots (<2 mm), stems, needles, and branches were analyzed. The results showed that the C, N, P contents and their ratios in P. yunnanensis were significantly influenced by season and organ, less affected by age. The C content of the middle-aged and young forests decreased continuously from spring to winter, whereas N and P first decreased and then increased. No significant allometric growth relationships were observed between P-C of the branches or stems in the young and middle-aged forests, whereas a significant allometric growth relationship existed for N-P of needles in the young stands, indicating that the P-C and N-P nutrient distribution patterns shows different trends in the organ level in different age stands. The pattern of P allocation between organs shows differences in stand age, with more allocation to needles in middle-aged stands and more allocation to fine roots in young stands. The N:P ratio in needles was less than 14, indicating that P. yunnanensis was mainly limited by N and increasing the application of N fertilizer would be beneficial for the productivity of this stand. The results will be helpful to nutrient management in P. yunnanensis plantation.